(untitled) (Teacher’s World: Journal of Education and Research, 2024)
This paper aims at identifying the main factors which influence learners’ motivation to seek admission into French Junior Certificate (FJC) course offered by the Institute of Modern Languages at the University of Dhaka. A sequential explanatory mix-method research design was used to address the research questions identified. Students, teachers, and database of FJC courses were chosen as data sources to collect both quantitative and qualitative data and evidences. A total of 269 students were selected for the quantitative data related to students’ background factors for the study. Besides, 12 students from six groups and 4 course teachers were selected randomly for collecting qualitative data related to factors that influence learners to pursue FJC course and challenges. The findings of the study suggest that the main motivational factors include international significance of French language, the nature of French language, desire for visiting France, love for French language and culture, desire to pursue higher studies in Francophone countries. Journal of Education and Research, 49 (1), 227-241